2020
DOI: 10.1080/16583655.2020.1778326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma-activated water treatment on seed germination and growth of mung bean sprouts

Abstract: The present work aimed to investigate the effect of plasma-activated water (PAW) on seed germination and seedling growth of mung bean sprouts. Distilled water was exposed to non-thermal plasma for 15, 30, 60, and 90 s to prepare PAW, which was defined as PAW15, PAW30, PAW60, and PAW90, respectively. The germination rate, growth characteristics, total phenolic and flavonoid contents were all maximized when mung bean seeds were treated by PAW15, then followed by a decline over the prolonged plasma activation tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 31 publications
6
32
0
Order By: Relevance
“…8.9 mm vs. 6.6 mm at 8 DAS) were obtained at a content of 1.5 mg L −1 NO 3 − (PAW I), which for the subsequent process of growth and development of the plant is a positive aspect, determining a higher force and implicitly increased production. Significant differences were also observed between PAW II treatment and control starting with 7 DAS, but the increases were less important compared to PAW I. www.nature.com/scientificreports/ Similar results were recorded by Fan et al 47 in a study regarding mung bean, where the positive effects on the seedlings growth decreased along with the increased discharge time. The lower positive effects of PAW II on the radicle and hypocotyls growth of lettuce seedlings can be due to the higher concentrations of reactive species (3.0 mg L −1 NO 3 − and 1.65 mg L −1 H 2 O 2 ) that might have had a detrimental effect, slowing the growth processes.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…8.9 mm vs. 6.6 mm at 8 DAS) were obtained at a content of 1.5 mg L −1 NO 3 − (PAW I), which for the subsequent process of growth and development of the plant is a positive aspect, determining a higher force and implicitly increased production. Significant differences were also observed between PAW II treatment and control starting with 7 DAS, but the increases were less important compared to PAW I. www.nature.com/scientificreports/ Similar results were recorded by Fan et al 47 in a study regarding mung bean, where the positive effects on the seedlings growth decreased along with the increased discharge time. The lower positive effects of PAW II on the radicle and hypocotyls growth of lettuce seedlings can be due to the higher concentrations of reactive species (3.0 mg L −1 NO 3 − and 1.65 mg L −1 H 2 O 2 ) that might have had a detrimental effect, slowing the growth processes.…”
Section: Resultssupporting
confidence: 83%
“…Similar results were recorded by Fan et al . 47 in a study regarding mung bean, where the positive effects on the seedlings growth decreased along with the increased discharge time. The lower positive effects of PAW II on the radicle and hypocotyls growth of lettuce seedlings can be due to the higher concentrations of reactive species (3.0 mg L −1 NO 3 − and 1.65 mg L −1 H 2 O 2 ) that might have had a detrimental effect, slowing the growth processes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…They concluded that the PAW may effectively improve the germination, the early development of wheat seedlings, but more importantly that the positive stimulation depends on the concentration of RONS in the PAW. In the same way, Fan et al [ 42 ] investigated the effect of PAW on mung bean sprouts by applying the distilled water exposed to nonthermal plasma for 15, 30, 60, and 90 s. They evaluated the PAW effect by measuring parameters, such as the germination rate, growth characteristics, total phenolic and flavonoid contents, and antioxidant enzyme activity, and they deduced that the PAW could stimulate the mung seed germination and growth. In general, the effect depended on the chemical composition of the different PAW.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification was also reported after treatment by PAW. Fan et al [ 56 ] reported a water absorption rate increase from 65% for control samples to 75% for treated mung beans. Sajib et al [ 57 ] reported a similar lipid or wax coat alteration of black gram due to the interactions of NO 2 − and H 2 O 2 with wax.…”
Section: Effects On Seed Surface Propertiesmentioning
confidence: 99%